The Effect of Lecturer Performance and Organizational Culture on Students' Learning Motivation in Higher Education Institutions - Sutawan, Komang; Burmansah, Burmansah; Susanto, Susanto; Widiyanto, Widiyanto; Rapiadi, Rapiadi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The research aims to know the influences of the performance of lecturers and cultural organizations on students' higher education motivation. There are some other problems, there are students who do not see lecturers as he explained, there are students who do not collect the class, there is a student who does not answer the question asked by teachers, and there is still a student who talks to the friend when lecturers explained the materials class in class. Researchers offer a solution to overcome problems with the motivation to study. The motivation to learn this is defined as a learning process using shared potential students, whether physical, mental, or emotional, to achieve educational objectives with insight into cognitive functioning, effective, and psychomotor optimally. The methodology used is descriptive quantitative research. The subject of the study was a student of the Buddhist Religious Education study program with 107 students. The sample in the study was 84 people. Data collection techniques in this study include using interviews and quisionary. The study used multiple linear regression analysis with a 5% error rate. The value of r square or R²=0.471=47.1% indicates that variables of student learning motivation can be explained by the performance variables of lecturers and organizational culture together at 47.1%. In other words, the performance variable of lecturers and organizational culture affects student learning motivation by 47.1%, and the remaining 52.9% are influenced by other factors not included in this research model. While R = 0.686, meaning lecturer performance variable, organizational culture has a solid relationship to learning motivation. Based on data analysis, it can be concluded that 1) there is a simultaneous influence between the performance of lecturers and organizational culture on learning motivation. 2) This shows that the more positive the lecturer's performance and the higher the organizational culture, the more motivation for students to learn in higher education institutions.